THE OPPORTUNITIES OF HEALTH TOURISM IN HUNGARY IN ADDRESSING THE HEALTH CHALLENGES OF AN AGING SOCIETY - Gabriella HELMECZI; Magdolna LÁCZAY (Oradea Journal of Business and Economics)
With an ageing population, the prevalence of musculoskeletal disorders is also rising significantly. This trend increases the burden on the health system and emphasizes the importance of health promotion and active ageing, for example through health tourism. The aim of my research is to explore the impact of Hungary’s ageing population and the increasing prevalence of musculoskeletal disorders on labour market participation and economic sustainability. The focus of the survey is the prevalence of musculoskeletal complaints. In my research I work with secondary data, which is reliable, collected from official sources. The analysis is based on reports from general practitioners and the Central Statistical Office, which provide detailed insights into the evolution of the number of patients with musculoskeletal complaints, data from spas. The data clearly show that prevention programs and therapeutic opportunities (e.g. thermal baths) can be of particular importance for the middle-aged and older age groups, who are the most affected.